Pelatihan Penerapan Model Pembelajaran Saintifik di Pondok Pesantren Al-Rusydiny Kecamatan Jeromaru Kabupaten Lombok Timur - Sawaludin; M. Alhadika; Sumardi, Lalu; Zubair, Muh.; Alqadri, Bagdawansyah; Hudori, Ahmad (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
In learning, the quality of the process is a concern for every teacher because the learning process determines learning outcomes. There are four competencies that must be possessed by teachers to be able to create a quality learning process, namely: content competence, pedagogic competence, social competence, and personality competence. This training aims to improve the pedagogical competence of teachers at PONPES Al-Rusydiny in applying learning models based on a scientific approach. The methods used in this training activity are lectures, brainstorming, discussions, and context analysis. To determine the impact of the training on teachers' understanding, measurements were taken using an online test based on Google Forms. Meanwhile, to determine the quality of the process, observation and interview techniques were used. Based on the test, it is known that their understanding of scientific learning models has increased. From the pretest, it is known that 12.5% of teachers have the wrong understanding of scientific learning models. As for the posttest, 100% of the teachers understood it well. Based on observation and interview techniques, it is known that the activities carried out are fun, interactive, and easy to follow. So, it can be concluded that the training conducted was able to improve the understanding of teachers at PONPES Al-Rusydiny about scientific learning models.